Creating value : successful business strategies - Mathur, Shiv Sahai; Kenyon, Alfred; ScienceDirect eBooks (Oxford ; Boston : Butterworth-Heinemann, 2001)
'Creating Value through Business Strategy' is the new edition of 'Creating Value: Shaping Tomorrow's Business', winner of the MCA price for best management in 1997. This new edition provides constructive guidelines to readers to open their minds to the challenges of creating value. It extends and updates the reasons for the choice of the individual offering as the strategy unit and intensifies and extends the challenges to standard approaches and conventional thinking. Updates to all the material from the first edition are included and new examples have been added throughout. Highly-acclaimed first edition, 'Creating Value: Shaping Tomorrow's Business', was winner of the MCA price for best management in 1997. Innovative, customer-led view of strategy that includes new examples and updated material. Controversially plays down the role of the international and global given the revolution in communications including the internet.
The framework in a nutshell -- Purpose, scope and basics; Fundamentals: the framework and its main building blocks -- Objectives: what is business strategy for?; Competitive and corporate strategy: why centred on offerings?; Understanding competitive positioning and strategy -- Differentiation creates private not public markets; Differentiation and its dimensions: classification of competitive strategies; Competitive positioning: differentiation and price; Competitive positioning in imperfect markets with dominant sellers; Competitive strategies for profit -- Competitive strategy: what makes it profitable?; Competitive strategy: dynamics of positioning; Resources and business strategy -- The theory of winning resources; Winning resources for the manager; The 'scissors' process for choosing a winning competitive strategy; Corporate strategy for clusters of offerings -- Corporate strategy's task is to build financial value; False and valid tests of corporate strategy; The corporate raider or catalyst; Valuable clusters of offerings: relatedness; How do managers develop successful corporate strategies?; Other implications of the framework -- Where in the world to sell and operate; Operating and organizational implications of this framework; Endpiece: business strategy for a new century; Glossary; References; Index.
Previous edition: 1997.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Business planning; Strategic planning; Success in business; BUSINESS & ECONOMICS -- Strategic Planning; Business planning; Strategic planning; Success in business; Strategische planning; Concurrentie; Electronic books